Measuring Power - Frankenberg, Elizabeth; Maluccio, John A. (International Food Policy Research Institute, 2003)
Much empirical work has approached the problem of how resource allocations are made within households from the perspective that if preferences differ, welfare outcomes depend on the power of individuals to exert their own preferences. Measures of power are therefore a central component of quantitative empirical approaches to understanding how different preferences translate into different welfare outcomes. Following most of the empirical studies in this genre, this chapter focuses on dynamics within couples.